On the approximation properties of Cesàro means of negative order of double Vilenkin – Fourier series - Tepnadze, T. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5 We establish approximation properties of Cesàro % (C,-α ,-β) means with α ,β ε (0,1) of Vilenkin – Fourier series. This result allows one to obtain a condition which is sufficient for the convergence of the means σ _n,m^-α,-β (x,y,f) to f(x,y) in the L^p-metric.